2019
DOI: 10.3390/jmse7090322
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Ocean Energy Technologies: A Systematic Review

Abstract: The increase of greenhouse gases (GHG) generated by the burning of fossil fuels has been recognized as one of the main causes of climate change (CC). Different countries of the world have developed new policies on national energy security directed to the use of renewable energies mainly, ocean energy being one of them. The implementation of ocean energy is increasing worldwide. However, the use of these technologies is not exempt from the generation of potential environmental impacts throughout their life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
“…As shown in Figure 1, the selected literature studied two oscillating surge WECs [22,25], one oscillating water column [21], three attenuators [14][15][16][17], two overtopping [3,23], four point absorbers [4,19,20,22], one vertical axis tidal [9], eight horizontal axis tidal [11][12][13]25], one Archimedes [13] and one tidal range [25].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 3 more Smart Citations